Parasite snail-host relationship of fasciola gigantica and lymnaea natalensis (1996)
The snail-host parasite interaction between L natalensis and F. gigantica was studied with particular emphasis on the effect of the relationship on the reproduction of the snail-host. Snails were exposed to 4 F. giganticamiracidium each and maintained on blanched and dried lettuce in aquaria at a temperature of 28-30°C. Growth, production of egg and shedding of metacercariae were monitored. Growth rate was reduced by about 19% in the infected snails relative to the uninfected control. Eggs were produced by the infected and uninfected control snails. However, it was observed that some of the masses produced by the infected snails did not contain eggs. Metacercariae production was found to suppress egg production. A negative linear relationship was discovered to exist between growth rate and metacercariae production with the latter being responsible for a 7% reduction in the growth of snails. These findings confirmed the fact that the parasite has a negative effect on the snail-host. However contrary to earlier observations, infected snails produced eggs although at a reduced rate. The present findings have provideda new insight into the dynamics of F. gigantic snail-host interactions